2017
DOI: 10.1016/j.bbalip.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Known unknowns of cardiolipin signaling: The best is yet to come

Abstract: Since its discovery 75 years ago, a wealth of knowledge has accumulated on the role of cardiolipin, the hallmark phospholipid of mitochondria, in bioenergetics and particularly on the structural organization of the inner mitochondrial membrane. A surge of interest in this anionic doubly-charged tetra-acylated lipid found in both prokaryotes and mitochondria has emerged based on its newly discovered signaling functions. Cardiolipin displays organ, tissue, cellular and transmembrane distribution asymmetries. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 181 publications
(203 reference statements)
3
88
0
2
Order By: Relevance
“…More detailed analysis of cyt c/CL interactions shows that the peroxidase function of cyt c may include several levels of “loosening” of the protein structure that are translated into different re-arrangements of the protein’s hexa-coordinated heme-iron environment [36, 37]. Detailed solid state NMR studies as well as crystallographic work suggest that small scale structural changes are sufficient for the initial induction of the peroxidase competence of cyt c /CL complexes [33, 38].…”
Section: Discussionmentioning
confidence: 99%
“…More detailed analysis of cyt c/CL interactions shows that the peroxidase function of cyt c may include several levels of “loosening” of the protein structure that are translated into different re-arrangements of the protein’s hexa-coordinated heme-iron environment [36, 37]. Detailed solid state NMR studies as well as crystallographic work suggest that small scale structural changes are sufficient for the initial induction of the peroxidase competence of cyt c /CL complexes [33, 38].…”
Section: Discussionmentioning
confidence: 99%
“…36 All these findings add to an emerging paradigm, namely that the myriad of different cellular lipid species, and in particular CL, have not just a supportive structural role, but are very actively involved in regulatory and signaling functions. 19,[37][38][39][40][41] …”
Section: Protein and Lipid Signaling In Mitophagy And Beyondmentioning
confidence: 99%
“…There are several “suspects” for the CL redistribution in the IMM. Given the essentiality of mitochondrial depolarization and potential involvement of redox-driven mechanisms, uncoupling proteins seem to be interesting candidates [80, 81]. The inter-membrane space translocation may be particularly challenging in terms of energetic expenditures.…”
Section: Asymmetry Is a Signal For Mitophagymentioning
confidence: 99%
“…Indeed, subsequent detailed studies revealed that CL peroxidation, catalyzed by cytochrome c, is required for the execution of intrinsic apoptosis in mammalian cells that have oxidizable CL species [91]. Detailed analysis of mechanisms and pathways involved in CL oxidation in apoptosis has been recently discussed in several reviews [37, 81, 9295]. Briefly, externalization of CL in damaged mitochondria strongly enhances its availability for the intermembrane space hemoprotein, cytochrome c. This encounter results in the formation of cytochrome c/CL complex in which the normally hexa-coordinated hemoprotein adopts the penta-coordinate organization allowing for the emergence of the peroxidase catalytic competence [91].…”
Section: Oxidation Elicits Intrinsic Apoptosismentioning
confidence: 99%